Osteochondral Fracture Lateral Femoral Condyle Treated with ORIF Using Z-Plasty: A Modification of Coonse and Adams Approach - Sanjay Agarwala; Ganesh S. Mohrir; Brijbhushan S. Mahajan (Case Reports in Orthopedics)
Osteochondral fractures of lateral femoral condyle are common in adolescents and young adults. They are usually caused by direct trauma or twisting injuries of the knee. We present a case of large osteochondral fracture of lateral femoral condyle involving the articular surface in a fifteen-year-old male with a positive history of significant weight gain of 5 kilograms in last six months. Blood investigations reported low vitamin D and testosterone levels with elevated alkaline phosphatase. Adequate exposure was achieved by doing Z-plasty of quadriceps apparatus. The fracture was treated with open reduction and internal fixation using Herbert's screws. Medical management in the form of vitamin D and calcium along with testosterone was given. After the surgery, full weight-bearing was allowed at three months. At one year followup, patient has good quadriceps function without any weakness of the muscle.